ANALISIS KOMPARASI PRESTASI BELAJAR ANTARA MAHASISWA AKTIF DAN TIDAK AKTIF BERORGANISASI DI PROGRAM STUDI NERS UNIVERSITAS ESA UNGGUL - Karyanah, Yayah (Indonesian Journal of Nursing Health Science, 2016)
Abstract Student organization is a forum for students to proceed both in learning and education acquired through activities conducted in formal and non-formal. Activeness of students in the organization have a role in learning achievement. In student organizations can foster soft skills naturally. Objective This study analyzes differences Learning Achievement of Students Active and switched on organizational At Ners Studies Program Esa Unggul University. The independent variable active and inactive student organization, Dependent Variables learning achievement. Sample 66 students of 4th semester and 6th semester Ners Studies Program Faculty of Health Sciences University of Esa Unggul Jakarta from 2015 to 2016. Sampling technique with purposive sampling. The research method uses kuantitatiif approach to the comparative method. The analytical method used is the analysis of the Independent-Sample T-Test. Collecting data using questionnaires and secondary data from the Department of Academic Administration. Research Hypothesis is Learning Achievement There is a difference between Active and Inactive Students Organize in Nursing Studies Program Esa Unggul University. Based on t-test value Sig .174, t count 1,378> t table 0.383. H0 failed rejected. Thus there is no significant difference between students learning achievement active in organizations and achievement of students do not actively organize. Students actively obtain the benefits of the activity in the student organizations that improve the Soft Skill that can be used in the workplace.Keywords: active and inactive students organize, learning achievement